TikTok: Educational Technology for Meaningful Learning of Exponential and Logarithmic Equations in Secondary Education - Diaz Porras, Jorge Alonso (2025)
This paper describes the use of TikTok as an educational technology for the meaningful learning of exponential and logarithmic equations in eleventh grade students at Liceo Regional de Flores, in Heredia, Costa Rica. With a pre-experimental design and quantitative approach, tests were applied to 195 students before and after the intervention. Initially, only 21.05% of females and 11% of males exceeded the score of 70 in first-degree equations, while 26.32% of females and 5% of males achieved this in exponential equations. A strategy based on short TikTok videos with visual explanations was implemented at the beginning of each class, followed by group discussion and immediate resolution of exercises. After the intervention, 94.74% of females and 85% of males exceeded the threshold in understanding logarithmic functions, and 89.47% of females and 83.99% of males in solving logarithmic equations. However, in combined equations and practical application, the percentages were lower. It is concluded that TikTok favors conceptual assimilation, but it is necessary to reinforce the transfer of knowledge to more complex contexts to consolidate meaningful learning.